2006
DOI: 10.1007/s00192-006-0233-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic single-dose prulifloxacin for catheter-associated urinary tract infection after tension-free vaginal tape procedure

Abstract: The purpose of the study was to evaluate whether antibiotic prophylaxis with a single dose of prulifloxacin after tension-free vaginal tape (TVT) procedure decreases catheter-associated urinary tract infections (UTIs). Patients undergoing TVT procedure receiving a single dose of prulifloxacin (600 mg) 10 h before catheter removal (n=54) were compared with historical controls who have had no treatment (n=60). All patients had an indwelling urethral catheter in situ for 24 h. Urine specimens for culture were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 24 publications
(25 reference statements)
1
30
0
Order By: Relevance
“…In a retrospective cohort of patients undergoing vaginal reconstructive surgery, prophylactic antibiotics decreased the risk of postoperative UTI in women requiring use of Foley catheterization at time of discharge [17]. This concept is further supported by Ghezzi et al [18] who reported prophylactic single-dose antibiotic therapy may help reduce the rate of UTIs after short-term urethral catheterization in women undergoing tension-free vaginal tape procedure.…”
Section: Discussionsupporting
confidence: 64%
“…In a retrospective cohort of patients undergoing vaginal reconstructive surgery, prophylactic antibiotics decreased the risk of postoperative UTI in women requiring use of Foley catheterization at time of discharge [17]. This concept is further supported by Ghezzi et al [18] who reported prophylactic single-dose antibiotic therapy may help reduce the rate of UTIs after short-term urethral catheterization in women undergoing tension-free vaginal tape procedure.…”
Section: Discussionsupporting
confidence: 64%
“…The value of chemoprophylaxis in lowering the incidence of UTIs in short-term catheterized patients is controversial [21]. Prophylactic chemotherapy may inhibit or promote UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is lower than previously reported studies. In review by Nygaard and Kreder, UTI rates were estimated at 17-85% after anti-incontinence procedures [21,25]. In a more recent retrospective study, Anger et al reported that 33.6% of patients undergoing a sling procedure experienced an UTI in the first 3 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…ACOG acknowledges the potential role for antibiotic prophylaxis during postoperative indwelling catheter use but makes no firm recommendation . The two studies examining antibiotic prophylaxis for routine postoperative catheterization did demonstrate a significant benefit in favor of this approach. However, routine prolonged indwelling catheterization is currently rarely needed after isolated MUS or even after MUS with pelvic reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%